3种保健功能性油脂中氯丙醇酯和缩水甘油酯的 污染调查与健康风险评估Contamination investigation and health risk assessment of chloropropanol esters and glycidyl esters in three health functional oils - 李益1,2，傅武胜1,2,3,4，倪蕾2，陈锦雄2,3，蔡家铭2，唐翠英1,2 LI Yi1,2, FU Wusheng1,2,3, 4, NI Lei2, CHEN Jinxiong2,3, CAI Jiaming2, TANG Cuiying1,2 (Zhongguo youzhi)
为对我国保健功能性油脂的市场监管和质量提升提供参考，随机采集3种市售保健功能性油脂（鱼油及其制品、葡萄籽油、红花籽油）,按照GB 5009.191—2024测定其氯丙醇酯（MCPDE）和缩水甘油酯（GE）的污染水平，并以点评估法进行慢性暴露评估和致癌性风险评估。结果表明：鱼油及其制品中3-MCPDE、2-MCPDE和GE的检出率分别为98.1%、83.3%和100%，平均含量分别为1.53、0.383、0.472 mg/kg，3-MCPDE和GE总体超标率(欧盟标准）为14.8%；葡萄籽油和红花籽油中3-MCPDE、2-MCPDE和GE的检出率均为100%，平均含量分别为0.998、0.470、0.883 mg/kg，3-MCPDE和GE总体超标率为26.7%；鱼油及其制品、葡萄籽油和红花籽油的3-MCPDE暴露量（成年人）分别为EFSA制定的每日耐受摄入量（TDI）的3.53%~4.46%、23.0%~29.1%，健康风险较低；采用EFSA（T25）和JECFA（BMDL10）估计GE的致癌风险，鱼油及其制品暴露边界值（MOE）最小值分别为3.71×105、0.873×105，大于安全阈值，致癌风险低，而葡萄籽油及红花籽油GE的MOE最大值分别为2.50×104、5.89×103，均小于安全阈值，存在致癌风险，需要优先关注。综上，3种油脂中普遍存在MCPDE、GE污染，但成年人群3-MCPDE暴露的健康风险低，而长期消费葡萄籽油或红花籽油的人群存在致癌风险，对GE的污染需要优先关注。To provide a reference for the market supervision and quality improvement of health functional oils in our country, three types of commercially available health functional oils (fish oil and its products, grape seed oil, and safflower seed oil) were randomly collected, and determined for the contamination levels of chloropropanol esters (MCPDE) and glycidyl esters (GE) according to the GB 5009.191-2024, and chronic exposure assessment and carcinogenic risk evaluation were conducted with the point estimation method. The results showed that the detection rates of 3-MCPDE, 2-MCPDE, and GE in fish oil and its products were 98.1%,83.3%, and 100%, respectively, with average contents of 1.53, 0.383 mg/kg and 0.472 mg/kg, and the total exceedance rate (EU standard) of 3-MCPDE and GE was 14.8%. The detection rates of 3-MCPDE, 2-MCPDE, and GE in grape seed oil and safflower seed oil were both 100%, with average contents of 0.998, 0.470 mg/kg and 0.883 mg/kg, respectively, and the total exceedance rate of 3-MCPDE and GE was 26.7%.The exposure levels of 3-MCPDE in fish oil and its proudcts, grape seed oil and safflower seed oil accounted for 3.53%-4.46%, 23.0%-29.1% of the EFSA′s tolerable daily intake (TDI) respectively, indicating low health risks. Carcinogenic risk of GE was estimated using EFSA (T25) and JECFA (BMDL10) methods. The minimum margin of exposure (MOE) for fish oil and its products were 3.71×105 and 0.873×105, respectively, which were above the safety threshold, indicating low carcinogenic risk. The maximum MOE for grape seed oil and safflower seed oil were 2.50×104 and 5.89×103, respectively, both below the safety threshold, indicating carcinogenic risk, warranting attention. In conclusion, MCPDE and GE contamination are common in the three oils. The health risk of 3-MCPDE exposure in the adult population is low. However, individuals consuming grape seed oil or safflower seed oil in the long term may face carcinogenic risks due to GE contamination, necessitating prioritized attention to GE contamination.